Centralised Supports for Writing in Higher Education and Their Applicability to Research, Teaching and Learning Contexts - Fogarty, Matthew (Journal of Academic Writing, 2020)
In 2018, as part of an EU COST Action (COST Action 15221 – www.werelate.eu), 43 academics, based at various higher education institutions in Europe, were asked about existing and desirable centralised support for writing, research, teaching and learning. This article draws on the academics’ responses. It uses that data to demonstrate the ways in which the learner-centred approach, typically adopted by writing centres, might function as a blueprint for a blended centralised support model for these four strands of higher education. In order to explore this idea, the article examines the reported support for research, as the data suggest that the majority of the centralised supports that currently exist at these institutions are designed primarily to support research. The study unpicks the mechanisms and approaches that are designed to ensure that research can be supported; it identifies what is effective in terms of supporting staff as researchers. From there, turning to the existing and desirable supports for writing, teaching and learning, I argue that, using a learner-centred writing centre model as inspiration, the structures which are currently in place to effectively support research can be modified and repurposed to more effectively support writing, teaching, and learning in higher education.